Survival Patterns of Human Prion Diseases in Spain, 1998–2018: Clinical Phenotypes and Etiological Clues - Tejedor-Romero, Laura; López-Cuadrado, Teresa; Almazán-Isla, Javier; Calero, Miguel; García López, Fernando J.; de Pedro-Cuesta, Jesús (Frontiers in Neuroscience, 2022)
Background: Human transmissible spongiform encephalopathies (TSEs) are a group of fatal neurodegenerative disorders of short duration. There are few studies on TSE survival. This study sought to analyse the survival and related factors of a TSE patient cohort, based on a nationwide surveillance system in Spain. Methods: Survival analyses were performed on 1530 cases diagnosed across the period 1998-2018 in Spain. We calculated median survival times and plotted survival curves using the Kaplan–Meier method for all cases, and for sporadic TSE (sTSE) and genetic TSE (gTSE). Crude and adjusted Cox proportional hazard models were used to identify variables associated with shorter survival. Findings: Median age at onset decreased from the sporadic forms to gTSE, and lastly to acquired TSE. Overall median and interquartile range (IQR) survival time was 5.2 (IQR, 3.0-11.7) months and 4.9 (IQR, 2.8-10.8) months in sporadic cases, and 9.0 (IQR, 4.9-over 12) months in genetic cases, p<0.001. Male sex, older age at onset, presence of 14-3-3 protein, typical MRI, and MM and VV polymorphisms at codon 129 were associated with shorter survival. gTSE showed higher survival in crude comparisons but not after adjustment. Interpretation: TSE survival in Spain replicates both the magnitude of that shown and the TSE entity-specific population patterns observed in Western countries but differs from features described in Asian populations, such as the Japanese. The reduction in differences in survival between gTSE and sTSE on adjusting for covariates and international patterns might support the view that gTSE and sTSE share causal and pathophysiological features.